Redo-EVAR After Surgical Repair in Ruptured Abdominal Aortic Aneurysm - Bozok, Şahin (J Cardiovasc Thorac Res, 2015)
Endovascular aneurysm repair (EVAR) is an adequate means for treating infrarenal abdominal aortic aneurysms (AAA). However, secondary interventions are required in approximately 15% to 20% of patients. The aim of this paper was to report our knowledge with stent grafts in secondary interventions after EVAR in a 73-year-old patient. One of the exceptional complications of EVAR are endoleaks which may lead to expansion of aneurysm and rupture if not repaired.